Massive pulmonary hemorrhage in enterovirus 71-infected hand, foot, and mouth disease - Dong Seong Lee; Young Il Lee; Jeong Bae Ahn; Mi Jin Kim; Jae Hyun Kim; Nam Hee Kim; Jong Hee Hwang; Dong Wook Kim; Chong Guk Lee; Tae Won Song (Korean Pediatric Society, 2015)
Hand, foot, and mouth disease (HFMD) is an acute, mostly self-limiting infection. Patients usually recover without any sequelae. However, a few cases are life threatening, especially those caused by enterovirus 71 (EV71). A 12-month-old boy was admitted to a primary hospital with high fever and vesicular lesions of the mouth, hands, and feet. After 3 days, he experienced 3 seizure episodes and was referred to our hospital. On admission, he was conscious and his chest radiograph was normal. However, 6 hours later, he suddenly lost consciousness and had developed a massive pulmonary hemorrhage that continued until his death. He experienced several more intermittent seizures, and diffuse infiltration of both lung fields was observed on chest radiography. Intravenous immunoglobulin, dexamethasone, cefotaxime, leukocyte-depleted red blood cells, fresh frozen plasma, inotropics, vitamin K, and endotracheal epinephrine were administered. The patient died 9 hours after intubation, within 3 days from fever onset. EV71 subgenotype C4a was isolated retrospectively from serum and nasopharyngeal swab by real-time reverse transcription-polymerase chain reaction. Here, we report a fatal case of EV71-associated HFMD with sudden-onset massive pulmonary hemorrhage and suspected encephalitis.